The heterogeneity of the Prologue text, as shown by orthographic data - Сергеевич Добровольский, Иван (Slavistica Vilnensis, 2004)
This study examines the distribution of several orthographic variants in the Old Church Slavonic Prologue in order to establish textological boundaries within the text. Five East Slavic Prologue manuscripts, dated from the 13th and, primarily, 14th centuries, serve as the corpus. The Prologue is a book of short saints’ lives, which, in the 12th century, included fragments from the Life of St Andrew the Fool. One may conclude that during the history of the text, the orthographic system of the Life became virtually the same as the orthographic system used in adjacent saints’ lives within the Prologue. In four of the five manuscripts under study, however, the distribution of several orthographic variants appears to be textologically bound, even though the text under analysis in each manuscript has been written by a single scribe; i.e., some of these variants occur only in the fragments from the Life of St Andrew the Fool and do not occur in the adjacent lives. It is generally argued that orthography is of no textological significance. However, despite multiple recopyings of manuscripts over the centuries, orthographic distinctions may be preserved between different parts of a single manuscript. Such distinctions enable us to trace the history of compiled texts.